AUDITORÍA DE GESTIÓN AL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL RURAL LOS ENCUENTROS. PERÍODO 2017 - Gordillo Rodríguez, Jeimmy Karen (2019)
The present research work, “MANAGEMENT AUDIT TO THE AUTONOMOUS DESCENTRALIZED RURAL PARISH GOVERNMENT LOS ENCUENTROS. PERIOD 2017”, it was carried out with the purpose of evaluating the levels of efficiency, effectiveness and economy in the fulfillment of the institutional objectives, in the use and management of public resources; In addition, a prerequisite for choosing the Degree and Degree in Accounting and Auditing, Public Accountant-Auditor, is fulfilled. The objectives proposed in the Management Audit were fully met; It began with the Preliminary Knowledge phase, which allowed the institution to be directly acquainted, gathering information and documentation necessary for the development of the audit; base for the planning and preparation of programs. In the Execution, following the procedures described in the program, the Internal Control System was evaluated by applying the control questionnaire, narrative cards that allowed to know the level of risk and confidence of each of the subcomponents, as well as the observance of the legal provisions and current regulations. Management indicators were applied to assess the degree of efficiency, effectiveness and economy in the management and use of public resources; the work papers that supported the findings were prepared. 5 Finally, the Management Audit report was issued, which establishes deficiencies that affect the achievement of institutional objectives, as well as the fulfillment of activities in 2017; The performance evaluation must be applied to each of the servers working in the Institution; The training should be constant and progressive that allow the updating of knowledge and thus promote efficiency and effectiveness in each of the entrusted activities. Finally, the most relevant conclusions of the work were highlighted, which through the evaluation of the Internal Control System allowed to know the levels of efficiency, effectiveness and economy, and through the application of indicators, institutional management was measured in order to determine the areas criticisms, which will be timely alternatives for solution and improvement in the future.